Effect of Work-Life Balance on Employee Performance Mediated by Job Satisfaction - Suwandi, Suwandi; Suhakim, Ade Imam (Universitas Pamulang, 2023)
Study this objective to determine the effect of work-life balance on employee performance mediated by job satisfaction. The population of this study consists of manufacturing employees in the Cikarang region, with a sample of 65 respondents. Purposive sampling is the retrieval method used to determine a sample's characteristics. Taking this sample has restrictions on certain types of individuals who provide required information. This is the primary data used in the study, collected from respondents who are manufacturing employees in the Cikarang region. Explain that there is a list of written questions that have been formulated, which was the previous respondent's record for answering them, and that this deep Thing is typically described with clarity via googleforms. Methods for analyzing data with the smart PLS program. The results of this study demonstrate that work-life balance has an effect on employee performance and that job satisfaction moderates the effect of work-life balance on employee performance. Unsatisfactory work will result in low morale and productivity, so the company must play an important role in procuring the facilities necessary to achieve work-life balance.